LAN Emulation over ATM. - Taylor, Martin (Computer communications.)
This paper is aimed at network designers and engineers who are looking at the deployment of ATM networking technology within or alongside an existing LAN infrastructure. The paper describes in detail how an ATM network can be made to emulate an existing Ethernet or Token Ring LAN. The benefit of this scheme is that it allows existing LAN applications to run over an ATM network with no modification and it provides for straightforward interconnection of existing Ethernet and Token Ring LANs with an ATM network. The paper provides a comprehensive tuturial on the LAN Emulation scheme, which is the subject of standardization by the ATM Forum, together with a discussion of the practical implications of the scheme and its application in real networks.